1997
DOI: 10.1046/j.1365-2141.1997.d01-2048.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of CD95 (FAS/APO‐1) in leukaemia‐lymphoma tumour lines

Abstract: Summary. Cross-linkage of the CD95 (FAS/APO-1) antigen is responsible for the induction of programmed cell death or apoptosis in a variety of normal and malignant cells of the haemopoietic system. In order to evaluate predominant expression of the CD95 gene in a cell lineage-specific manner, we have determined the CD95 expression patterns in cell lines of myeloid, T-, pre-B-or B-cell origin as well as those established from Hodgkin's disease (HD). Our results reveal constitutive transcriptional activation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 25 publications
(29 reference statements)
1
28
0
1
Order By: Relevance
“…Proteolytic activation of caspase-3 may result from either extrinsic apoptotic signals, such as CD95L (FasL), after binding to specific receptors (CD95, Fas), or intrinsic apoptotic signals from mitochondria, such as expression of BCL-2 family members that can lead to activation of caspase-9 and release of cytochrome c. 22 Previous in vitro studies have shown that the CD95/CD95L pathway is active in ALCL cells. 32,33 Furthermore, overexpression of BCL-2 family proteins 13,34 may also contribute to caspase-3-mediated cell death in ALK-positive ALCL.…”
Section: Discussionmentioning
confidence: 99%
“…Proteolytic activation of caspase-3 may result from either extrinsic apoptotic signals, such as CD95L (FasL), after binding to specific receptors (CD95, Fas), or intrinsic apoptotic signals from mitochondria, such as expression of BCL-2 family members that can lead to activation of caspase-9 and release of cytochrome c. 22 Previous in vitro studies have shown that the CD95/CD95L pathway is active in ALCL cells. 32,33 Furthermore, overexpression of BCL-2 family proteins 13,34 may also contribute to caspase-3-mediated cell death in ALK-positive ALCL.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro studies using cell lines derived from systemic ALCL cases have provided evidence that t(2;5)-positive ALCL cells express CD95 and undergo CD95-induced apoptosis. 45 Clusterin, recently reported to be specifically expressed in ALCL cell lines and tumors, also may be involved. 46 Clusterin (also known as sulfated glycoprotein 2, human apolipoprotein A-I, J) is a highly conserved glycoprotein, which among its other functions, promotes cell death.…”
Section: Discussionmentioning
confidence: 99%
“…25,26,37 Shima and colleagues 38 examined the relationship between CD95 expression and sensitivity to death receptor-mediated apoptosis in several multiple myeloma cell lines and patient specimens. This report demonstrated that CD95 expression correlates to some degree with sensitivity to CD95 death signaling, however, this trend was not consistent over all the cell lines investigated.…”
Section: Discussionmentioning
confidence: 99%